Impact of digital tablets on the work of interior design practitioners - Hamre, Kellie E., author; Clemons, Stephanie, advisor; Gibbs, Richard, committee member; Banning, James, committee member (Colorado State University. Libraries, 2013)
The purpose of this exploratory research study is to explore how interior design practitioners utilize digital tablets during the design process. Of particular interest is if and how design practitioners are using the digital tablet when generating new ideas for the client within the schematic design phase. Understanding how interior designers use digital tablets during the design process will offer insights concerning their adoption process of a new technology. This phenomenological study was conducted with practicing interior designers in the state of Colorado with a wide range of practice experience. Participants completed a short demographic survey and answered open-ended questions regarding their personal experiences with the digital tablet in their work processes. The findings of this study shed light on why interior designers use digital tablets in their work process, in addition to providing insight on why they don't use them for certain tasks. The category of participant's motivations for using the digital tablet in design projects included four themes: (1) communication, (2) information gathering, (3) document management and (4) business productivity. The communication theme had three sub-themes that emerged (1) electronic, (2) photographic and (3) visual presentation. The theme of information gathering includes two sub-themes of (1) collection of information and (2) idea generation. Within the category of participant experiences, there were two themes that emerged. They were (1) impact on work processes and (2) potential of digital tablet during design process. The theme, impact on the work processes, had two sub-themes that emerged: (1) advantages and (2) disadvantages. While the use of digital tablets is on the rise, much is yet to be known about how and why digital tablets are used. This study provides and exploratory foundation, supported by innovation of behavior theory, providing initial insight into the use of digital tablets in the design process.
Keywords: design process; technology; practitioners; interior design; digital tablets